2014
DOI: 10.1186/1471-2318-14-114
|View full text |Cite
|
Sign up to set email alerts
|

How are falls and fear of falling associated with objectively measured physical activity in a cohort of community-dwelling older men?

Abstract: BackgroundFalls affect approximately one third of community-dwelling older adults each year and have serious health and social consequences. Fear of falling (FOF) (lack of confidence in maintaining balance during normal activities) affects many older adults, irrespective of whether they have actually experienced falls. Both falls and fear of falls may result in restrictions of physical activity, which in turn have health consequences. To date the relation between (i) falls and (ii) fear of falling with physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
128
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(156 citation statements)
references
References 30 publications
14
128
1
10
Order By: Relevance
“…A 7% of the patients experienced head injuries, with loss of consciousness, a 4% sustained fractures and 4% died due to an injury produced by the fall 2 . Moreover, except physical injuries, falls and disequilibrium can lead to 'fear of falling' which further restricts every day activities 8,12 , leads to depression 12 and reduces physical exercise such as walking 13 .…”
Section: Fall-related Injuriesmentioning
confidence: 99%
“…A 7% of the patients experienced head injuries, with loss of consciousness, a 4% sustained fractures and 4% died due to an injury produced by the fall 2 . Moreover, except physical injuries, falls and disequilibrium can lead to 'fear of falling' which further restricts every day activities 8,12 , leads to depression 12 and reduces physical exercise such as walking 13 .…”
Section: Fall-related Injuriesmentioning
confidence: 99%
“…Research must focus on building associations between PAL and falling risk or FOF without any bias (27). However, it is emphasized that sufficient physical activity and higher physical fitness might contribute to preventing falls and FOF (6,28,29 of physical inactivity (27). Our results showed that PAL might be ineffective on falling risk and FOF.…”
Section: Discussionmentioning
confidence: 75%
“…In previous studies, the general consensus is that physical activity has a close relationship with falling risk and FOF (8,27). Research must focus on building associations between PAL and falling risk or FOF without any bias (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alltagsorientierte körperliche Trainingsprogramme zielen darauf ab, die Körperfunktionen zu verbessern und mobilitätsbezogene Risikofaktoren wie Stürze zu reduzieren (Jefferis et al, 2014). Sie können in monofaktorielle Trainingsprogramme (Cumming et al, 1999;Steultjens, Dekker, Bouter, Jellema, & Bakker, 2004;Clemson, Mackenzie, Ballinger, Close, & Cumming, 2008;Costello, & Edelstein, 2008;Sherrington et al, 2008;Davis et al, 2010;Sherrington, Tiedemann, Fairhall, Close, & Lord, 2011;Leland, Elliott, O'Malley, & Murphy, 2012) und in multifaktorielle Trainingsprogramme (Steultjens et al, 2004;Costello, & Edelstein, 2008;Peterson, & Clemson, 2008, Sherrington et al, 2008Davis et al, 2010;Sherrington et al, 2011;Leland, et al, 2012) eingeteilt werden.…”
Section: Wirkweise Körperlicher Trainingsprogrammeunclassified